Brand Awareness & Brand Image: Key Point Coffee's Success in Influencing Purchasing Decisions in Serang City - Yoga Adiyanto; Dhany Isnaeni Darmawan; Deni Sunaryo; Iman Hickmatullah; Achmad Fazi Alam (Smart Society, 2025)
The coffee industry in Indonesia, particularly in Serang City, has shown significant growth in recent years. This growth is driven by an increasing interest among the public in coffee as a lifestyle, as well as the emergence of various coffee brands, including Point Coffee, which has managed to maintain its position despite facing increasingly fierce competition. This study aims to analyze the influence of brand use and brand image on consumer purchasing decisions of Point Coffee in Serang City. This study uses a quantitative approach with a survey method, where primary data is collected through questionnaire distributed to consumers. Data analysis was carried out using Structural Partial - based Equation Modeling (SEM). Least Squares (PLS). The results of the study show that the brand use and brand image has a significant influence on purchasing decisions. Brand image was found to have more dominant influence than brand use in influencing purchasing decisions.These findings provide important insights for Point Coffee in development more effective marketing strategies, with a focus on strengthening brand image and increasing brand exposure in the market. This study also contribute to the development of literature on the influence of brand use and brand image in the coffee industry sector, especially in non-metropolitan areas.